2012
DOI: 10.1007/s13311-012-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Pharmacotherapy

Abstract: Summary The benzodiazepine receptor agonists (BzRAs) a melatonin receptor agonist and a histamine antagonist have all been approved as hypnotics. Beyond their differing mechanisms of action, they have differences in pharmacokinetics, and among the BzRAs differences in receptor subtype affinity and formulations, which provides the physician with broad options for tailoring therapy to each patient's specific needs. Consistent with their specific pharmacokinetics and formulations, these Food and Drug Administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 88 publications
0
76
0
9
Order By: Relevance
“…A breadth of research has demonstrated the efficacy of both pharmacological (e.g., benzodiazepine hypnotics) and behavioral (cognitive behavioral therapy for insomnia, CBT-I) interventions for the treatment of insomnia and sleep disturbances [59][60][61]. Comparisons between pharmacotherapy and behavioral interventions have demonstrated comparable treatment effects, with pharmacotherapy offering a more immediate impact on sleep and behavioral interventions linked to greater long-term and sustained treatment gains [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A breadth of research has demonstrated the efficacy of both pharmacological (e.g., benzodiazepine hypnotics) and behavioral (cognitive behavioral therapy for insomnia, CBT-I) interventions for the treatment of insomnia and sleep disturbances [59][60][61]. Comparisons between pharmacotherapy and behavioral interventions have demonstrated comparable treatment effects, with pharmacotherapy offering a more immediate impact on sleep and behavioral interventions linked to greater long-term and sustained treatment gains [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment effectiveness exists for both forms of intervention, it is important to note that no study has examined comparative efficacy or effectiveness of these interventions among individuals with a history of substance use disorders. This limitation of existing work is likely due to the fact that pharmacotherapy for insomnia is typically not recommended for individuals with a history of substance use disorders owing to the risk of the development of dependence [61]. For this reason, additional research among substance use populations is needed.…”
Section: Discussionmentioning
confidence: 99%
“…16 This approach is distinct from current insomnia drugs, most of which promote sleep by enhancing sleep signaling via gamma-aminobutyric acid (GABA) inhibitory effects. 17 The suvorexant phase-3 development program in insomnia patients was comprised of two 3-month pivotal trials, each of which evaluated two age-adjusted (non-elderly/elderly) dose regimes of 40/30 mg and 20/15 mg, 8 and a 1-year trial of 40/30 mg. 7 The primary objective of the trials was to establish the efficacy, safety, and tolerability of the 40/30 mg dose. By design, fewer…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia and several other sleep disorders occur with disproportionate prevalence among the elderly, and as such hypnotic medications are commonly used by elderly individuals [1][2][3][4][5][6]. Extensive research data on hypnotic drug disposition and effects in the elderly population indicates that older persons may have reduced metabolic clearance of hypnotic medications (leading to higher plasma concentrations), increased intrinsic sensitivity to hypnotic drugs, or both [7][8][9].…”
Section: Introductionmentioning
confidence: 99%